Research on factors affecting audit quality of financial statements of listed companies in Vietnam - Khuat, Thai Tai (H. : ĐHQGHN, 2020)
The topic’s focus is to identify factors affecting audit quality of financial reports of listed companies in Vietnam by independent auditing firms. The research objects are listed companies on the Ho Chi Minh City and Hanoi Stock Exchanges.